IN STATE MANAGEMENT PROCESSING SYSTEM OF CUSTOMS ADMINISTRATION - Dosmyrza, Достан (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
In his article the author considers legal aspects of customs administration in system of state management, and also system of means of realization of customs politics as basic tool of customs administration.